Envoltorio y pedernal: Octavio Paz y Luis Cardoza y Aragón sacando chispas. O de las intuiciones ch’ixi sobre la identidad en El Laberinto de la soledad y Guatemala las líneas de su mano - Urízar, Julio (2025)
This work compares the metaphors associated with mestizo identity and subjectivity in two essays from Latin American literature: El laberinto de la soledad (1950) by Octavio Paz and Guatemala, las líneas de su mano (1955) by Luis Cardoza y Aragón. The notions of identity and subjectivity are read as enveloping and sparkling processes, where discomfort and contradiction are inherent to the affirmative process of the Mexican and Guatemalan experiences. It is concluded that the texts express in their most poetic facet an experience of mestizo identity and subjectivity similar to Ch’ixi subjectivity, proposed by the Bolivian sociologist Silvia Rivera Cusicanqui as a space of friction and discomfort that does not allow the pacification of unity, open to the possibility of new and plural recognitions.